Alfabetização e letramento em salas multifases da educação do campo, no contexto do Pacto Nacional pela Alfabetização na Idade Certa (PNAIC) - Siqueira, Maria Aparecida de Oliveira (2016)
This research, entitled Literacy in multiphase rooms of Rural Education, in the context of the Pacto Nacional pela Alfabetização na Idade Certa (PNAIC), is linked to the Graduate Program in Education of the Federal University of Mato Grosso, College of Rondonópolis (PPGEDU/UFMT/CUR), research line of Languages, Culture and Knowledge Construction, and was hosted by the research group Alfabetização e Letramento Escolar (ALFALE). The focus of this research is on the following question: How is the teaching of native language in multiphase rooms with children from early years of elementary school, in countryside schools, from the perspective of teaching illiterate children in the context of PNAIC? In order to answer this question, the main purpose of the research is to analyze the process of teaching the native language, focusing the teaching on children starting elementary school, triggered by two teachers of multiphase rooms in rural schools, in the context of PNAIC. In line with this general objective, three specific objectives were defined: a) Identify the strategies used by the teachers on the process of teaching, regards the organization of time and space; b) Identify how the teachers work the axes, currently suggested to native language education; c) Identify aspects worked for the formation of PNAIC used in practice by the teachers. This qualitative study of ethnographic type used questionnaire, semi-structured interviews, planning documents and field research as tools for data gathering and observation protocols to record the daily practices of the teachers. This research is based on the design of supported language of Bakhtin, understood as historical, concrete and social. The literature review of scientific work (theses, dissertations and articles in journals and conference proceedings), in the period 2006-2015, showed that the binomial "literacy and letters in Rural Education" is still little discussed on the basis of data consulted. Data were analyzed from the Axes proposed by PNAIC for native language teaching. The results indicate that the work with the identification of letters, syllables and words for understanding the alphabetic writing system (SEA) and phonological reflection of the writing of the words was more evident in the practice of Teacher Val, performing it every day she was assisted. Moreover, the axes Text Writing and Linguistic Knowledge Production were more evident in the practice of teacher Lu. The axis Reading Comprehension was evidenced in 100% of the days observed both in the practice of Lu as well as Val. Research has shown that both the practice of Lu as well as Val prevail elements of a more traditional concept of the native language education. However, both have tried with very great effort to ensure a quality job in creating opportunities for the advancement of their students, first in reading as well as in writing, incorporating their practices to the classroom methodology aspects suggested by the formation of PNAIC. Finally, the observations inform that the rural schools 14 de Agosto and Marajá, despite being located in the countryside, work along the lines of an urban school, because, at least in the observed period, the teachers gave little emphasis on specific valuation context the students are inserted.